IMPLEMENTASI METODE TALAQQI PADA PROGRAM RUMAH QUR'AN DI DESA SARAMPAD - Latipah, Euis; Maspitah, Pipit; Yunita, Risma (Dirasa Islamiyya: Journal of Islamic Studies, 2022)
Memorizing the holy verses of the Qur'an is a noble practice that brings many benefits and goodness for the perpetrators in this world and the hereafter. But in fact, most Muslims find it heavy and difficult to memorize. The ability of Tahfidz students in memorizing the Qur'an is different, therefore the right method is needed from the many methods of memorizing the Qur'an. Rumah Qur'an Goes To Sarampad Village uses the Talaqqi method in learning Tahfidzul Qur'an. The formulation of the problem in this study is how to implement the Talaqqi method in learning Tahfidzul Qur'an at the Qur'an House of STAI Al-Azhary KKN Group 12. This type of research is field research and is a type of qualitative research. In this study, the actual situation in the implementation of the Talaqqi method in teaching Tahfidzul Qur'an at the Qur'an House of KKN STAI Al-Azhary Group 12 is described. The data collection methods in this study used observation, interviews, and documentation. The results of this study indicate that the implementation of the Talaqqi method in Tahfidzul Qur'an learning at the Qur'an House of STAI Al-Azhary Group 12 is carried out with 4 main activities as follows: First, Opening. Second, the core learning activities which include the memorization process, the process of depositing verses, and muraja’ah letters that have been memorized. Third, closing activities. Fourth, evaluation.